Catalyst for preparing p-bromobenzonitrile by ammonia oxidation method, preparation method and use thereof
By using vanadium-containing composite oxide-supported vanadium-containing composite oxide catalysts, the problem that existing catalysts are difficult to meet industrial needs is solved, and the efficient, economical and environmentally friendly preparation of bromobenzonitrile is achieved, and the strength and activity of the catalyst are improved.
Patent Information
- Application Number
- CN202310127777.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-02-17
AI Technical Summary
The existing per-bromobenzonitrile catalysts are difficult to meet the industrial requirements of high strength, long life, high load and high activity and high selectivity. At the same time, the process route is complex and raw materials are rare, making it difficult to achieve large-scale industrial production.
The vanadium-containing composite oxide-containing catalyst supported by silicon-aluminum composite oxide is prepared by spray drying. The active component is a vanadium-containing multi-component composite oxide, and combined with a silicon-aluminum composite oxide support to regulate the structure and performance of the catalyst.
It improves the strength and wear resistance of the catalyst, extends the service life of the catalyst, enhances the activity and selectivity of the catalyst, and realizes the efficient preparation of bromobenzonitrile, with a simple process route, easy access to raw materials, low cost, and environmentally friendly.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for preparing p-bromobenzonitrile by ammonia oxidation method, a preparation method and application thereof, and belongs to the technical field of organic chemistry and also to the technical field of organic fine chemicals. Background Art
[0002] p-Bromobenzonitrile is also known as p-bromobenzonitrile. As an important bromine-based fine chemical, p-bromobenzonitrile is mainly used in the fields of medicine, pigments and organic synthesis. With the development of the medicine and fine chemical industries, the demand for p-bromobenzonitrile in the domestic and foreign markets is increasing, and the market prospects are very good.
[0003] Literature reports that p-bromobenzonitrile can be prepared by a variety of methods. Japanese patent JP7372152 discloses the preparation of p-bromobenzonitrile from p-bromobenzoic acid by ammoniation and dehydration, and patent WO9805630 discloses the preparation of p-bromobenzonitrile using p-bromobenzaldehyde as a raw material. These methods have long process routes, and the raw materials are hard to obtain, making them difficult to realize industrial production. p-Bromobenzonitrile can also be prepared using p-bromotoluene as a raw material. For example, the literature (Angew.Chem.Int.Ed.2013,52,10573-10576; Org.Lett.2013,15,4194-4197; Eur.J.Org.Chem.2014,4115-4122; Chem.Commun.,2015,51,5085-5088; J.Am.Chem.Soc.2016,138,3294-3297; Nat.Commun.2017,8,15240; Chem.Eur.J.2020,26,14070-14074) can all use p-bromotoluene to prepare p-bromotoluene. However, these methods usually require special or expensive reagents, or the production process or product processing process is complicated, and continuous production is not possible, etc., which makes it difficult to achieve large-scale industrial production. p-Bromobenzonitrile can also be prepared by a method of heterogeneous catalytic ammoxidation using p-bromotoluene as a raw material. The method of producing p-bromobenzonitrile by ammoxidation has the advantages of simple process route, continuous production, strong production capacity, significant economic benefits, simple product post-processing, high purity, and environmental friendliness. The core is the development of a highly active and highly selective ammoxidation catalyst. German Patent 256129 discloses the preparation of p-bromobenzonitrile by ammoxidation reaction using VOPO4 as a catalyst in a fixed bed reactor. The large amount of reaction heat released during the reaction is difficult to remove, thereby reducing the yield and seriously affecting the service life of the catalyst. Chinese Patent CN1252043C discloses a method for preparing p-bromobenzonitrile, in which a vanadium-chromium five-component catalyst is prepared by spray drying, and the yield of preparing p-bromobenzonitrile by catalyzing the ammoxidation reaction of p-bromotoluene can reach 90%. However, the catalyst still finds it difficult to meet the industrial requirements for high strength, long life, high load, high activity and high selectivity of the catalyst. Summary of the invention
[0004] A technical problem to be solved by the present invention is to provide a catalyst for preparing p-bromobenzonitrile by an ammoxidation process.
[0005] Another technical problem to be solved by the present invention is to provide a method for preparing the above catalyst.
[0006] The third technical problem to be solved by the present invention is to provide the use of the above catalyst.
[0007] In order to solve the above-mentioned first technical problem, the present invention provides a catalyst for preparing bromoxynil by an ammoxidation method.
[0008] The catalyst is a vanadium-containing composite oxide catalyst supported by a silicon-aluminum composite oxide. The active component of the catalyst is a vanadium-containing multi-component composite oxide, and the composition is expressed as: VTi a Cr b Sn c D d E e O x ; Wherein D is one of scandium, lanthanum, cerium, samarium, europium, and ytterbium, and E is at least one of beryllium, magnesium, calcium, strontium, or barium; a=0.2-2.5; b=0.1-1.3; c=0.01-1.0; d=0-0.8; e=0-0.5; x is determined according to the valence balance of the above elements. The active components are uniformly mixed with the silicon-aluminum composite oxide carrier to form composite microspheres; the sum of the weights of the active components in the catalyst accounts for 10-80% of the total weight of the composite microspheres, preferably 30-70%. The diameter of the composite microspheres ranges from 20 to 120 μm, and the average diameter is 40 to 60 μm.
[0009] The silicon-aluminum composite oxide is used as a carrier, which is a composite of silicon oxide and aluminum oxide in a certain proportion, wherein the weight percentage of aluminum oxide in the carrier is 1-100%, preferably 5%-80%. In the silicon-aluminum composite oxide carrier, silicon oxide is made of silica sol as a precursor, and aluminum oxide is made of one or more of Al-MOF materials, pseudo-boehmite, boehmite, nano-alumina, aluminum sol, aluminum nitrate, etc. as a precursor; the silicon sol is evenly mixed with at least one aluminum oxide precursor, and calcined at high temperature to form a silicon-aluminum oxide composite carrier. The silicon sol can be acidic, alkaline or neutral silicon sol. The aluminum oxide precursor includes one or more of Al-MOF materials, pseudo-boehmite, boehmite, nano-alumina, aluminum sol, aluminum nitrate, etc., wherein the Al-MOF materials include MIL (Materials Institute Lavoisier), CAU (Christian-Albrechts-University), DUT (Dresden University of Technology), PCN (Porous coordination network) and other types, such as MIL-53, MIL-53-NH2, MIL-96, MIL-100, MIL-110, MIL-68, NH2-MIL-101(Al), MIL-1 2. MIL-14, MIL-27, MIL-32, MIL-34, MIL-64, MIL-69, MIL-91, MIL-116, MIL-118, MIL-120, MIL-121 , MIL-122, MIL-160, DUT-4, CAU-1, CAU-3, CAU-4, CAU-6, CAU-8, CAU-10, CAU-10-H, CAU-10-NO2, CA U-10-NH2, CAU-10-OH, CAU-10-CH3, CAU-10-OCH3, CAU-11, CAU-12, CAU-13, CAU-15, CAU-23, AlFu, etc. After the addition of aluminum oxide precursors to form silicon-aluminum composite oxides, on the one hand, the effect of active centers and carriers can be strengthened, the loss of active components can be reduced, and the strength and wear resistance of the catalyst can be improved, greatly extending the service life of the catalyst; on the other hand, by adding aluminum oxide precursors to form a composite carrier, the ratio and strength of L acid (Lewis acid) and B acid (Bronsted acid) in the carrier can be regulated, thereby adjusting the acidity and alkalinity of the catalyst, the redox ability and the coordination ability with the reactants, and improving the activity and selectivity of the catalyst; thirdly, the special structure and morphology of the aluminum oxide precursor can be used to regulate the structure and morphology of the catalyst, including particle size, specific surface area, pore volume, etc., thereby regulating the physical, chemical and catalytic properties of the catalyst.
[0010] In order to solve the above second technical problem, the technical solution designed by the present invention is as follows:
[0011] The present invention adopts a spray drying method to prepare the catalyst, and the specific steps are: firstly, a silicon oxide precursor silica sol is mixed evenly with at least one of an aluminum oxide precursor Al-MOF material, pseudo-boehmite, boehmite, nano-alumina, aluminum sol, aluminum nitrate, etc. in a certain proportion, and the catalyst active component VTi is converted into the catalyst active component VTi. a Cr b Sn c D d E e O x The precursors are dissolved, mixed and uniformly mixed with the above-mentioned silicon aluminum oxide precursor used as a carrier in a certain proportion to form a suspension or slurry; sprayed and formed by a high-speed centrifugal spray dryer, and then activated at high temperature to form a multi-component inorganic oxide microsphere catalyst supported by a micron-sized silicon aluminum composite oxide carrier. The activation temperature is generally between 623 and 973K, and the best temperature range is 673 to 873K. The activation time is generally 2 to 15 hours, and the optimal activation time range is 3 to 8 hours.
[0012] The catalyst active component precursor refers to a compound containing at least one element among V, Ti, Cr, Sn, D or E, and the ratio of the sum of the amount of V, the sum of the amount of Ti, the sum of the amount of Cr, the sum of the amount of Sn, the sum of the amount of D and the sum of the amount of E in each precursor is 1:a:b:c:d:e; when d is zero, none of the precursors contains the D element; when e is zero, none of the precursors contains the E element.
[0013] When preparing the catalyst, any precursor can be an oxide, salt, acid or base containing at least one element of V, Ti, Cr, Sn, D or E. For example, V2O5 or NH4VO3 can be used for vanadium; TiCl4, TiCl3, TiOSO4, Ti(C2O4)2, H2TiO3, TiO2 or tetrabutyl titanate can be used for titanium; Cr(NO3)3·9H2O, Cr2O3, CrO3 or (NH4)2Cr2O7 can be used for chromium; SnO2, SnO, SnCl4, SnCl2, Sn(NO3)2, SnSO4, stannous methanesulfonate, stannous ethylsulfonate or stannous propylsulfonate can be used for tin; and scandium, lanthanum, cerium, Samarium, europium, ytterbium, etc. can be prepared using rare earth nitrates, acetates, sulfates, (p-toluene)sulfonates, chlorides, oxides, etc.; beryllium can be prepared using BeO, BeCl2 or Be(NO3)2, etc.; magnesium can be prepared using MgO, MgCl2 or Mg(NO3)2·6H2O, etc.; calcium can be prepared using CaCl2·6H2O, Ca(OH)2 or Ca(NO3)2, etc.; strontium can be prepared using SrCl2, Sr(OH)2 or Sr(NO3)2, etc.; barium can be prepared using BaCl2, Ba(OH)2 or Ba(NO3)2, etc. When preparing the solution, a commonly used method known in the art is used, for example, V2O5, etc. is dissolved in H2C2O4 aqueous solution to prepare the solution, while KCl, KNO3, K2CO3, etc. are directly dissolved in water to prepare the solution.
[0014] In order to solve the third technical problem mentioned above, the catalyst provided by the present invention is used for preparing p-bromobenzonitrile by ammoxidation reaction of p-bromotoluene.
[0015] Taking p-bromotoluene as a raw material, ammonia and oxygen undergo gas phase ammoxidation reaction under the action of a catalyst to obtain p-bromobenzonitrile; the reaction yield is 80-95%. The optimal process conditions for preparing p-bromobenzonitrile by ammoxidation reaction of p-bromotoluene using the catalyst are as follows: reaction temperature 633-723K, air to p-bromotoluene molar ratio 10-50, ammonia to p-bromotoluene molar ratio 1-10, catalyst load 20-100g / (kgcat·h). Under a quartz tube fluidized bed reactor with an inner diameter of 30mm and stable reaction conditions, the conversion rate of p-bromotoluene can be higher than 98%, and the molar yield of p-bromobenzonitrile can reach more than 90%.
[0016] Compared with other methods, the present invention has the advantages of cheap and readily available reaction raw materials, simple process route, environmental friendliness, low cost, high yield, etc., especially the catalyst strength and wear resistance are greatly improved, the life is greatly extended, the catalyst activity and product selectivity are also improved. The ammoxidation reaction catalyst has high selectivity and activity; the preparation method is simple, the cost is low, and it has good thermal stability and mechanical strength. It can be used in both fixed bed and fluidized bed reactors and has good application value. DETAILED DESCRIPTION
[0017] The following examples will help to further understand the present invention, but they are not intended to limit the present invention.
[0018] Example 1
[0019] Add 18g of Al-MOF material CAU-10-NH2 to 140g of silica sol with a content of 30% and stir to mix into a uniform suspension; dissolve 69.43g of H2C2O4·2H2O in 300mL of 80℃ distilled water, slowly add 33.43g of V2O5 to react until no gas is produced, then add 128.89g of Ti(C2O4)2, 73.71g of Cr(NO3)3·9H2O, 9.57g of SnCl4 and 2.73g of Mg(NO3)2, and slowly add to the mixed suspension of the above silica sol and Al-MOF after forming a uniform solution. After stirring evenly, the catalyst precursor is obtained by high-speed spray centrifugal drying, dried at 110℃ in a muffle furnace, and then gradually heated to 600℃ and kept warm for 4 hours. After natural cooling, it is set aside. The active composition of the catalyst is: VTi 1.5 Cr 0.5 Sn 0.1 Mg 0.05 O 6.5 The active component content is 60%, and the weight percentage of alumina in the silicon-aluminum composite oxide carrier is 30%. The average particle size of the catalyst is 55μm, the bulk density is 0.92g / ml, and the specific surface area is 65m 2 / g, and the wear rate is 2.1%.
[0020] 100 g of the solid catalyst was loaded into a quartz tube fluidized bed reactor with an inner diameter of 30 mm, the molar ratio of the reaction raw materials was: p-bromotoluene: NH3: Air = 1:4:25, the reaction temperature was 673±1K, and the catalyst load was 50 g / (kgcat·h). After 8 hours of reaction, the conversion rate of p-bromotoluene was 98.7%, and the molar yield of p-bromobenzonitrile was 89.5%.
[0021] Example 2
[0022] Comparative Example: The catalyst preparation method is the same as Example 1, except that the Al-MOF material CAU-10-NH2 is not added to the silica sol, the amount of 30% silica sol is 200 grams, and the catalyst active components are the same. The average particle size of the catalyst is 52μm, the bulk density is 0.89g / ml, and the specific surface area is 71m 2 / g, the attrition rate was 3.8%, which was more than 80% higher than that of Example 1; therefore, the catalyst prepared in Example 1 was more wear-resistant and stronger. The experimental conditions for the catalytic ammoxidation of p-bromotoluene were the same as those in Example 1. After 8 hours of reaction, the conversion rate of p-bromotoluene was 98.5%, and the molar yield of p-bromobenzonitrile was 81.3%.
[0023] Embodiments 3 to 8
[0024] The catalyst formulation is different, and the reaction conditions are the same as in Example 1. The results are shown in the following table:
[0025]
[0026] It is well known to those skilled in the art that the catalyst of the present invention containing other promoters can also be prepared according to the above method. During preparation, the corresponding precursor materials of other promoter components can be replaced in proportion with reference to the above examples to obtain the desired catalyst. The corresponding precursors of other promoter components can be oxides, salts, acids or bases thereof.
Claims
1. A catalyst for preparing p-bromobenzonitrile by an ammoxidation process, characterized in that: The catalyst is a vanadium-containing composite oxide catalyst supported by a silicon-aluminum composite oxide. The active component of the catalyst is a vanadium-containing multi-component composite oxide. The composition is expressed as: VTi a Cr b Sn c D d E e O x ; wherein D is one of scandium and ytterbium, and E is one of beryllium and barium; a = 0.2 to 2.5; b = 0.1 to 1.3; c = 0.01 to 1.0; d = 0.2 to 0.8; e = 0.02 to 0.05; x is determined according to the content of each element in the above composition according to the valence balance; The silicon-aluminum composite oxide refers to a substance formed by a composite of silicon oxide and aluminum oxide in a certain ratio; wherein the silicon oxide uses silica sol as a precursor, and the aluminum oxide uses one or more of Al-MOF materials, pseudo-boehmite, boehmite, nano-alumina, aluminum sol, and aluminum nitrate as a precursor, and the silica sol and at least one aluminum oxide precursor are uniformly mixed and calcined at a high temperature to form a silicon-aluminum oxide composite carrier; The active component is uniformly mixed with the silicon-aluminum composite oxide carrier to form composite microspheres; the weight percentage content of the active component in the catalyst is 10-80%; the diameter of the composite microspheres ranges from 20 to 120 μm, and the average diameter is 40 to 60 μm.
2. The catalyst according to claim 1, characterized in that: The silica sol is acidic, alkaline or neutral silica sol; in the aluminum oxide precursor, the Al-MOF material includes MIL CAU, DUT, PCN types.
3. The catalyst according to claim 2, characterized in that: The Al-MOF material is MIL-53, MIL-53-NH2, MIL-96, MIL-100, MIL-110, MIL-68, NH2-MIL-101 (Al), MIL-12, MIL-14, MIL-27, MIL-32, MIL-34, MIL-64, MIL-69, MIL-91, MIL-116, MIL-118, MIL-120, MIL-121, MIL-122, MIL-160, DUT-4, CAU-1, CAU-3, CAU-4, CAU-6, CAU-8, CAU-10, CAU-10-H, CAU-10-NO2, CA U-10-NH2, CAU-10-OH, CAU-10-CH3, CAU-10-OCH3, CAU-11, CAU-12, CAU-13, CAU-15, CAU-23 or AlFu.
4. The catalyst according to claim 1, 2 or 3, characterized in that: The weight percentage of aluminum oxide in the silicon-aluminum composite oxide carrier of the catalyst is 5-80%.
5. The catalyst according to claim 4, characterized in that: The weight percentage content of the active component in the catalyst is 40-70%.
6. The method for preparing the catalyst according to any one of claims 1 to 5, characterized in that: The preparation method adopts high-speed centrifugal spray drying, and the specific steps are: 1) uniformly mixing a silicon oxide precursor silica sol with at least one of an aluminum oxide precursor Al-MOF material, pseudo-boehmite, boehmite, nano-alumina, aluminum sol, and aluminum nitrate to obtain a silicon aluminum oxide precursor used as a carrier; 2) Convert to the catalyst active component VTi a Cr b Sn c D d E e O x The precursors are dissolved, mixed and uniformly mixed with the silicon aluminum oxide precursor used as a carrier in a certain proportion to form a suspension or slurry; 3) Spraying into shape by a high-speed centrifugal spray dryer; 4) high temperature activation to form a multi-component inorganic oxide microsphere catalyst supported by a micron-sized silicon-aluminum composite oxide carrier; the high temperature activation temperature is 623-973K, and the activation time is 2-15 hours; The catalyst active component precursor refers to a compound containing at least one element among V, Ti, Cr, Sn, D or E, and the ratio of the sum of the amount of V, the sum of the amount of Ti, the sum of the amount of Cr, the sum of the amount of Sn, the sum of the amount of D and the sum of the amount of E in each precursor is 1:a:b:c:d:e.
7. The method for preparing the catalyst according to claim 6, characterized in that: The temperature of the high temperature activation is 673-873K, and the activation time is 3-8 hours.
8. The method for preparing the catalyst according to claim 6 or 7, characterized in that: The catalyst active component precursor is an oxide, salt, acid or base containing at least one element of V, Ti, Cr, Sn, D or E.
9. The method for preparing the catalyst according to claim 8, characterized in that: The catalyst active component precursor is V2O5 or NH4VO3; TiCl4, TiCl3, TiOSO4, Ti(C2O4)2, H2TiO3, TiO2 or tetrabutyl titanate; Cr(NO3)3·9H2O, Cr2O3, CrO3 or (NH4)2Cr2O7; SnO2, SnO, SnCl4, SnCl2, Sn(NO3)2, SnSO4, stannous methanesulfonate, stannous ethylsulfonate or stannous propylsulfonate; nitrates, acetates, sulfates, p-toluenesulfonates, chlorides and oxides of rare earths; BeO, BeCl2 or Be(NO3)2; BaCl2, Ba(OH)2 or Ba(NO3)2.
10. Use of the catalyst according to any one of claims 1 to 5, characterized in that: The catalyst is used for preparing p-bromobenzonitrile by ammoxidation of p-bromotoluene.
Citation Information
Patent Citations
Process for preparing para-bromo benzonitrile
CN1252043C
DE256129A
Process for the preparation of organic nitriles
WO1998005630A1
Aromatic ammoxidation fluidized bed catalyst, preparation method and application
CN106268890A